Brain Abscess in Children: A Rare but Serious Infection. (May 2018) - Sahbudak Bal, Zumrut; Eraslan, Cenk; Bolat, Elif; Avcu, Gulhadiye; Kultursay, Nilgun; Ozkinay, Ferda; Kurugol, Zafer; Vardar, Fadil
Brain abscess is a rare disease in childhood requiring prompt medical and/or surgical treatment. The objective was to review presentation, management, and outcome of brain abscess in children. We reviewed the clinical and radiological features and outcomes of 18 children (10 females, 8 males), with a median age of 48 months (range 1-182), that presented with brain abscesses and admitted to a tertiary pediatric infectious department between December 2010 and January 2017. One (5.5%) patient underwent craniotomy and 14 (77.7%) had burr hole aspirations. The most common localization was the frontal lobe (33.3%). The survival rate was 94.4%, and long-term neurological sequelae affected 27.7% of the patients. Empiric treatment choices require knowledge of common pathogens and local resistance. The most predominant infections were still upper respiratory infections. Clinicians may treat the children with appropriate choice and duration of antibiotic treatment for upper respiratory tract infections.